PPARγ/NF‐κB and TGF‐β1/Smad pathway are involved in the anti‐fibrotic effects of levo‐tetrahydropalmatine on liver fibrosis - Yu, Qiang (J Cell Mol Med, 2021)
Liver fibrosis is a necessary stage in the development of chronic liver diseases to liver cirrhosis. This study aims to investigate the anti‐fibrotic effects of levo‐tetrahydropalmatine (L‐THP) on hepatic fibrosis in mice and cell models and its underlying mechanisms. Two mouse hepatic fibrosis models were generated in male C57 mice by intraperitoneal injection of carbon tetrachloride (CCl4) for 2 months and bile duct ligation (BDL) for 14 days. Levo‐tetrahydropalmatine was administered orally at doses of 20 and 40 mg/kg. An activated LX2 cell model induced by TGF‐β1 was also generated. The results showed that levo‐tetrahydropalmatine alleviated liver fibrosis by inhibiting the formation of extracellular matrix (ECM) and regulating the balance between TIMP1 and MMP2 in the two mice liver fibrosis models and cell model. Levo‐tetrahydropalmatine inhibited activation and autophagy of hepatic stellate cells (HSCs) by modulating PPARγ/NF‐κB and TGF‐β1/Smad pathway in vivo and in vitro. In conclusion, levo‐tetrahydropalmatine attenuated liver fibrosis by inhibiting ECM deposition and HSCs autophagy via modulation of PPARγ/NF‐κB and TGF‐β1/Smad pathway.